Promoting Digital Entrepreneurship to mitigate the impacts caused by the COVID-19 pandemic - Carvalho, Dárlinton Barbosa Feres; Cunha, Alice Ferreira; Corrêa, Fábio; Mendonça, Fabrício Molica de (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2021: Anais do XVII Simpósio Brasileiro de Sistemas de Informação, 2021)
The COVID-19 pandemic forced governments to impose harsh social restrictions as part of the strategy to deal with the situation, forcing society to adapt quickly. In response to this emergency, we offered training in technological skills (i.e., development of information systems) and behavioral skills (i.e., entrepreneurship mindset) in an effort to empower people to better tackle the situation. This paper explains the foundations considered in the proposal of the intervention, as well as the results obtained. Through development in line with university extension principles, the intervention promotes the empowerment and participation of citizens in creating digital solutions that enable society to overcome its problems, especially those caused by the imposition of social distance. Taking advantage of web-centric software platforms, participants of the offered training were able to build support systems for online businesses. The results achieved by the 48 graduates reinforce the viability and importance of citizen participation in the creation of innovations based on digital entrepreneurship.